A new species from Central Anatolia in Turkey, Atriplex turcica (Chenopodiaceae) - Başköse, İsa; Yaprak, Ahmet Emre (Phytotaxa, 2019)
Atriplex turcica is here described and illustrated as a new species of tribe Chenopodieae (sect. Teutliopsis), from the Central Anatolia, Turkey. Morphologically, Atriplex turcica is characterized by the combination of stem, leaf characters, fruit shape, and seed morphology. Additional details on its diagnosis, description, chromosome numbers (diploid 2n=2x=18 and tetraploid 2n=4x=36), distribution and habitat, diagnostic key, and comparisons to related species (A. laevis and A. prostrata) are also provided.